2001
DOI: 10.1096/fj.00-0604fje
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in cervical carcinoma cells by peptide aptamers that bind to the HPV‐16 E7 oncoprotein

Abstract: Human papillomaviruses (HPV) of the high-risk type are causally involved in human tumors, in particular cervical carcinoma. Expression of the viral oncogenes E6 and E7 is maintained in HPV-positive tumors, and it was shown that E6 and E7 of HPV-16 can immortalize human keratinocytes, the natural host cells of the virus. Expression of the viral genes is also required for maintenance of the transformed phenotype. The oncogenic activity of the E6 and E7 oncoproteins is mediated by their physical and functional in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…The present results suggest that decreased expression of E7 likely participates in the decreased viability of HPV-positive tumor cells. Nauenburg et al (2001) have shown that E7-binding peptide aptamers induced apoptosis in E7-expressing cells, whereas E7-negative cells were not affected. However, how E6/E7 transcription is downregulated by ST remains to be characterized.…”
Section: Discussionmentioning
confidence: 97%
“…The present results suggest that decreased expression of E7 likely participates in the decreased viability of HPV-positive tumor cells. Nauenburg et al (2001) have shown that E7-binding peptide aptamers induced apoptosis in E7-expressing cells, whereas E7-negative cells were not affected. However, how E6/E7 transcription is downregulated by ST remains to be characterized.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that expression of HPV-16 E7 induces apoptosis in human fibroblasts and keratinocytes (1,20,44,51) and in the lens of transgenic mice (22,33). However, E7 has also been found to inhibit apoptosis induced by TNF-␣ in human fibroblasts (46), and E7-binding peptide aptamers induced apoptosis in cervical cancer cells (32). According to our results, differences in the level of E7 protein expressed in the various systems used for those studies may provide an explanation for such discrepancies.…”
Section: Vol 77 2003 Enhanced Expression Of Hpv-16 E7 By Codon Optimentioning
confidence: 99%
“…[7][8][9] Several approaches have been explored to interfere with the HPV-induced abnormal proliferation by blocking the E7 activity at either gene or protein level, e.g., by phosphorothioate oligonucleotides, 10 short interfering RNA 11 and aptamers. 12 Intracellular immunization has provided new chances for interfering with the function of predetermined intracellular targets by directing antibodies in scFv format to specific compartments of mammalian cells. 13 The intracellular antibodies (intrabodies) can specifically recognize the target antigen in the intracellular environment and counteract its function with a not yet clarified mechanism of action, spanning from forming antigen-antibody complexes to diverting the target-antigen to unusual compartments.…”
mentioning
confidence: 99%